Which Works Better for Kampus Merdeka MSIB: Ads or Content? - Ramadhan, Syahrul; Oktarici, Eddo Nanda (Journal of Applied Business Administration, 2025)
This study aims to evaluate the influence of social media advertising and content marketing on the brand awareness of the Kampus Merdeka MSIB program at Infinite Learning. The research uses a quantitative approach with non-probability sampling through purposive sampling techniques. A total of 160 students who had been exposed to Infinite Learning's advertisements or content on Instagram participated as respondents, and data were collected through an online questionnaire. Data analysis was carried out using the SEM-PLS method. The results indicate that social media advertising has a positive and significant effect on brand awareness, while content marketing has a positive but not significant effect. Although the individual effects differ, the combination of both strategies shows a significant influence on increasing brand awareness. These findings suggest that the synergy between advertising and content strategies on social media is more effective than applying them separately in building brand awareness for Infinite Learning’s MSIB program.